Falling Behind or Catching Up? Cross-Country Evidence in Intra-Generational Wages Mobility through Pseudo-Panels - Marco Lilla (Luxembourg Income Study (LIS), 2016)
The paper aims to encompass evidence on wage distribution and inequality with micro-mobility measures for several countries in the 2000s, by applying pseudo-panel methodology to microdata from the LIS database. Hence, different paths in term of wage growth or stagnation, increasing or declining inequalities and wages convergence over time emerge from comparison across countries. Finally, cohort-based measures of micro-mobility are compared to the corresponding ones obtained from true panel component for some countries.
Keywords: D31; J31; D63; 330; Intra-generational Mobility; wage; inequality